My first day - Phung, Nguyen Quang; Huynh, Kim Lien (Make Me a World, 2021)
"This is no ordinary first journey. The rainy season has come to the Mekong Delta, and An, a young Vietnamese boy, sets out alone in a wooden boat wearing a little backpack and armed only with a single oar. On the way, he is confronted by giant crested waves, heavy rainfall and eerie forests where fear takes hold of him. Although daunted by the dark unknown, An realizes that he is not alone and continues to paddle. He knows it will all be worth it when he reaches his destination"--